Direito dos animais: uma análise acerca dos efeitos da proibição da crueldade contra animais não humanos à luz do sistema jurídico brasileiro - Duarte, Tiago Flores (Universidade do Vale do Rio dos Sinos, 2023)
Since 1988, Brazil has had its current Federal Constitution, peculiarly different from its predecessors, by virtue of establishing innovative norms in the face of the old Constitutions of that country, such as item VII of the first paragraph of its article 225, which prohibits cruelty against non-human animals in Brazil. Using systemic-constructivist perspective, this dissertation aims to verify the scope with which Brazilian rules, principles and judicial decisions guarantee the right to non-suffering in favor of non-human species in Brazil, to the point that it is possible to identify a response to the research problem of this study, which can be defined as follows: in view of the recognition of animal sentience today, to what extent has the prohibition of cruelty against non-human animals been incorporated by the Brazilian legal system? Divided into three parts, in the first chapter, an analysis is made of the Rights of Animals in Brazil based on Brazilian federal legislation. Then, the legislative initiatives arising from the State of Rio Grande do Sul and the Municipality of Porto Alegre on the Rights of Animals are verified, as well as the main decisions of the Brazilian Judiciary Power regarding the prohibition of cruelty against non-human animals in Brazil; in the second chapter, the concept of cruelty against non-human species is instituted through the perspectives of the Brazilian legal system, the global scientific system and the moral field, so that one can observe the convergences and divergences between these perspectives; in the third and last chapter, taking into account the legal system of the European Union, which represents a world reference regarding the matter, it is proposed to investigate the legislation related to animal experimentation for the development and commercialization of cosmetic products in Brazil, against non-human animals in that country. In the end, it is observed that the Brazilian legal system guarantees the right not to suffer to non-human animals in specific situations in Brazil, depending on the human purposes to be achieved through the suffering of these beings.
Keywords: Direito dos Animais; Sistema jurídico brasileiro; Senciência animal; Crueldade; Cosméticos; Animal Rights; Brazilian legal system; Animal sentience; Cruelty; Cosmetics; ACCNPQ::Ciências Sociais Aplicadas::Direito